The antepartum stillbirth syndrome: risk factors and pregnancy conditions identified in the INTERGROWTH-21st Project - Hirst, J; Villar, J; Victora, C; Papageorghiou, A; Finkton, D; Barros, F; Gravett, M; Giuliani, F; Purwar, M; Frederick, I; Pang, R; Cheikh Ismail, L; et al. (Wiley, 2016)
Objectives: We aimed to identify risk factors for antepartum stillbirth including fetal growth restriction, amongst women with well-dated pregnancies and access to antenatal care. Design: Population-based, prospective, observational study Setting: Eight international urban populations Population: Pregnant women and their babies enrolled in the Newborn Cross-Sectional Study of the INTERGROWTH-21st Project. Methods: Cox proportional Hazard models were used to compare risks amongst antepartum stillborn and liveborn babies. Main outcome measures: Antepartum stillbirth was defined as any fetal death after 16 weeks of gestation before the onset of labour. Results: Of 60 121 babies, 553 were stillborn (9.2 per 1000 births), of which 445 were antepartum deaths (7.4 per 1000 births). After adjustment for site, risk factors were low socio-economic status, Hazard ratio (HR): 1·6 (95% CI 1·2-2·1); single marital status, 2·0 (1·4-2·8); age  40 years, 2·2 (1·4-3·7); essential hypertension 4·0 (2·7-5·9); HIV/AIDS 4·3 (2·0-9·1); preeclampsia 1·6 (1·1-3·8), multiple pregnancy 3·3 (2.0-5·6) and antepartum haemorrhage 3.3 (2.5-4.5). Birth weight < 3rd centile was associated with antepartum stillbirth, 4.6 (3.4-6.2). The greatest risk was in babies not suspected to have been growth restricted antenatally, 5.0 (3.6-7.0). The population attributable risk of antepartum death associated with SGA diagnosed at birth was 11%. Conclusions: Antepartum stillbirth is a complex syndrome associated with several risk factors. Although small babies are at higher risk, current growth restriction detection strategies only modestly reduced the rate of stillbirth.